2018
DOI: 10.1016/j.ssmph.2018.04.001
|View full text |Cite
|
Sign up to set email alerts
|

What’s up with the self-employed? A cross-national perspective on the self-employed’s work-related mental well-being

Abstract: Although many governments actively stimulate self-employment, their work-related mental well-being remains understudied. The aim of current study is to investigate the mental well-being of different types of self-employed, testing whether mental well-being differences among self-employed are explained by the presence of work characteristics that are in accordance with the ideal-typical image of the “successful entrepreneur” (e.g. creativity, willingness to take risks, innovativeness, high intrinsic motivation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 32 publications
1
39
0
5
Order By: Relevance
“…Wheeler et al [26] identified that some Australian irrigators experienced high levels of psychological distress nationally; higher than dryland farmers or the Australian population. Gevaert et al [85] found farmers, self-employed, and own account workers have worse mental health compared to medium-to-large employers and liberal professions. Ulrich et al [102] identified that stress was significantly higher in farmworkers compared with non-farmworkers only in one farming period.…”
Section: Systematic Review Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wheeler et al [26] identified that some Australian irrigators experienced high levels of psychological distress nationally; higher than dryland farmers or the Australian population. Gevaert et al [85] found farmers, self-employed, and own account workers have worse mental health compared to medium-to-large employers and liberal professions. Ulrich et al [102] identified that stress was significantly higher in farmworkers compared with non-farmworkers only in one farming period.…”
Section: Systematic Review Resultsmentioning
confidence: 99%
“…Age of farmers and the association with mental health issues has been discussed in-depth in the literature. Overall, younger farmers experienced higher levels of stress-related symptoms [62,85,88,179]. This was most likely associated with higher debt levels.…”
Section: Systematic Review Resultsmentioning
confidence: 99%
“…Running one’s own business—i.e., being self-employed—seems to be of pronounced importance for the older group and their stability in mental health. Gevaert et al investigated the phenomenon of self-employed people’s wellbeing in 28 European countries [75]. Their findings highlight individual characteristics, such as motivation and the ability to identify opportunities, and, furthermore, that medium and large employers present high levels of wellbeing, but not self-employed in dependencies, such as farmers and freelancers.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, worldwide Governments started promoting self-employment [8]. The EU 2020 Employment Strategy is significant in this regard: it recognizes entrepreneurship and self-employment as key factors for achieving smart, sustainable and inclusive growth and as a way to create new jobs [9].…”
Section: Introductionmentioning
confidence: 99%
“…The EU 2020 Employment Strategy recognizes entrepreneurship and self-employment as key factors for achieving sustainable, smart and inclusive growth and as a way to create new jobs [9]. In this framework, young people continue to be challenged by the unpredictability of the labor market since a mismatch between the skills possessed, acquired during the training, and those required by employers [8]. Also, the concept of career is assuming different meanings.…”
Section: Introductionmentioning
confidence: 99%